ANALISIS PENERAPAN KURIKULUM MERDEKA BELAJAR DI SMA NEGERI SEKOTA PADANGSIDIMPUAN - Hasrida Hutabarat; Muhammad Syahril Harahap; Rahmatika Elindra (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
Abstract This study aims to determine the application of the independent learning curriculum at SMA Negeri in Padangsidimpuan city. This research was conducted from SMA N 1, to SMA N 8 Padangsidimpuan. This research used descriptive qualitative research method. Informants from this study were the vice principal of the curriculum, 3 teachers, and 3 students from each school. Data collection techniques used in this study were observation, questionnaires, interviews and documentation. Data analysis techniques are data reduction, data presentation and conclusion drawing or verification. Based on the results of research conducted at SMA Negeri Sekota Padangsidimpuan, from the results of the questionnaire filled out by 28 informants, it was obtained an average of 84.1071 with the category